(untitled) (Eurasian Journal of Research, Development and Innovation, 2025)
Training specialists in the field of cybersecurity is a highly relevant issue today, gaining even more importance with the global technological advancement and widespread use of the internet. The increasing number of cyberattacks and cybercrimes, as well as the need for governments and corporations to ensure information security, have intensified the demand for cybersecurity specialists. This article analyzes the existing experiences of training cybersecurity specialists in various countries around the world. Revisiting the development of cybersecurity and the training of specialists based on modern requirements will help strengthen cooperation between countries and create an opportunity to achieve global stability in the field of cybersecurity